Juridical Study on Notaries Who Commit Criminal Acts Based on Law Number 2 of 2014 concerning the Position of Notary - Made Sada; Erikson Sihotang; Ni Ketut Wiratny (CV. Syntax Corporation Indonesia, 2024)
Notaries as public officials have significant legal responsibilities in making authentic deeds. This research aims to analyze the legal procedure for summoning a notary as a witness in a case of alleged fraud or embezzlement. The research method used is normative research, by analyzing relevant laws and literature regarding the criminal responsibility of notaries based on Law Number 2 Year 2014. The results show that the summoning of notaries as witnesses by investigators must fulfill the provisions stipulated in the law, including approval from the Notary Honor Council. In addition, there are significant differences in the procedure after the issuance of Constitutional Court Decision Number 49/PUU-X/2012. This research emphasizes the need to evaluate regulations related to summoning notaries to ensure independence and speed up the legal process. The implications of the findings include increased awareness of notaries and socialization to the public regarding their roles and responsibilities. This research shows the importance of increasing notaries' awareness of their legal responsibilities and the need for reform of legal procedures to speed up the summoning and examination of notaries. In addition, strengthening regulations and socializing to the public regarding the role of notaries can help prevent errors in the making of authentic deeds.